LA GERENCIA SOCIAL Y LA RENTABILIDAD SOCIAL: EL CASO DE LA COMUNIDAD CAMPESINA DE HUAYACONDO-AYACUCHO - Tito Huamaní, Pedro Leonardo (2011)
This paper is an analysis of applying the concepts of social management in a community organization. The Rural Community Huayacondo Tambillo district, province and department of Ayacucho, through communal practice is achieving impressive results that improve the quality of life of its citizens. The organizational instrument, bring down infant mortality rates, combat chronic malnutrition among children in the community and raise the level of organic, to optimally manage and use natural resources comes to be the Community Development Committee (CODECO ). The CODECO is the parent organization that brings together the community of water users Board, Parent Association (APAFA), mothers' clubs, Glass of Milk, Water Allocation Board for Services (JAAS), the association of breeders guinea pigs, in wine association, etc. Being a permanent discussion forum raised the level of awareness of the community, with consequent favorable results for the welfare of the rural community. Through empowerment and community leadership to develop the different organizations linked to CODECO, to date the Rural Community may exhibit the following achievements: • Annual income economic families increased by 57% compared to the previous year, allowing them to spend more on food. • Improved access to safe water by 95% and basic sanitation by 90%. • Decreased 6.9% of a total of 20% of the incidence of chronic malnutrition in children under 3 years. • Formalizing organizational structure to the Local and Regional Government, as is recognized CODECO ordinance. This allows them to show to their members and communities as a strong and sustainable community organization. • Construction and use of improved stoves in each home, with technical assistance ONG CARE Peru and public institutions. • Promotion and active participation of women at different levels of organization. Seen this way, the social management becomes an instrument of organizational management, with the participation and democratic style of decision, where the protagonist of the change is the same farmer, who through various organizations contributes creatively in solving problems facing their community.